2015
DOI: 10.1016/j.pnsc.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Structural and spectroscopic analysis of wurtzite (ZnO)1−x(Sb2O3)x composite semiconductor

Abstract: The structural, vibrational and impedance analysis for (ZnO) 1 À x (Sb 2 O 3 ) x composite synthesized by solid state reaction technique were carried out in the present investigation. X-ray diffraction (XRD) study showed that (ZnO) 1 À x (Sb 2 O 3 ) x composite has hexagonal (wurtzite) crystal structure. Variation in lattice constants with Sb-doping indicated the proper incorporation of Sb dopant in ZnO host matrix. The results of Raman spectroscopy test suggested the signature of E 2 (high) and E 1 (TO) Raman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 36 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…XRD patterns of all ZnO NRs AR layers exhibit all the characteristics of the diffraction peaks of ZnO, along with a strong Si phase, which are located at 34.38 • (002) and 69.26 • (001), respectively, as shown in Figure 4. The observed diffraction peaks confirm the perfect crystal of ZnO, having the hexagonal wurtzite phases of ZnO materials [35] along with the monocrystalline crystalline phase of Si. This examination clearly deduces the growth of single crystalline ZnO NRs on a Si surface via the low-temperature solution method, followed by annealing at 250 • C for 1 h. The growth of ZnO NRs on the surface of the textured Si wafer were analyzed to examine the crystalline phases by XRD measurements.…”
Section: Resultssupporting
confidence: 52%
“…XRD patterns of all ZnO NRs AR layers exhibit all the characteristics of the diffraction peaks of ZnO, along with a strong Si phase, which are located at 34.38 • (002) and 69.26 • (001), respectively, as shown in Figure 4. The observed diffraction peaks confirm the perfect crystal of ZnO, having the hexagonal wurtzite phases of ZnO materials [35] along with the monocrystalline crystalline phase of Si. This examination clearly deduces the growth of single crystalline ZnO NRs on a Si surface via the low-temperature solution method, followed by annealing at 250 • C for 1 h. The growth of ZnO NRs on the surface of the textured Si wafer were analyzed to examine the crystalline phases by XRD measurements.…”
Section: Resultssupporting
confidence: 52%
“…There was no ZnSrelated peak detected in 30 min-and 60 min.-annealing samples. In spite of this, the most obvious ZnS-related peaks (JCPDS card no: 05-0566) were observed in sample of 90 min-annealing which indicated that enough amount S-inclusion might create weak Zn(O,S) host matrix [15]. While 30 min.-annealing samples had (100) preferential orientation, 60 min.…”
Section: Resultsmentioning
confidence: 92%
“…. The d values of ZnO nanoparticles calculated using the Bragg's relation, d = λ/(2 sin θ ), were 0.28, 0.26, 0.25, 0.19, 0.16, 0.14, 0.137, and 0.135 nm corresponding to (1 0 0), (0 0 2), (1 0 1), (1 0 2), (1 1 0), (1 0 3), (1 1 0), and (2 0 1) planes, respectively, which can be indexed to that of hexagonal wurtzite structure of ZnO . The lattice constant of ZnO nanoparticles was 0.325 nm, while the crystallite size calculated using Scherrer's equation [37] was 20.9 nm.…”
Section: Resultsmentioning
confidence: 99%